Conduction mechanism and dielectric properties of BiFeO3–BaTiO3 solid solutions - Shankar S.; Kumar M.; Ghosh A.K.; Thakur O.P. (My University, 2025)
The first measurements are reported for the frequency-dependent conductivity of (1−x)BiFeO3–xBaTiO3 (x = 0.10, 0.15 and 0.30) solid solutions in the frequency range of 100–106 Hz and in the temperature range of 50–300 °C. Powder X-ray diffraction confirms the formation of solid solutions. The dielectric properties were seen to improve with increasing BaTiO3 (BT) content. The conductivity (AC and DC) measurements reveal an inverse variation of the frequency exponent ‘s’ with temperature, high density of states and thermally activated process. The calculated density of states was found to be N(Ef) = 80.2 × 1032 eV−1 cm−1 at 1 kHz and 50 °C for BiFeO3–10 % BaTiO3 (BFO–10 % BT) solid solution. The impedance spectroscopy analysis confirms the presence of grain and grain boundary affecting the conductivity. Our results provide the first unambiguous evidence of conduction in crystallite BFO–BT solid solutions through correlated-barrier-hopping model. © 2014, Springer Science+Business Media New York.